Observations of flexure and the rheology of oceanic lithosphere - Watts, A; Zhong, S (2000)
The principal evidence for the long-term (i.e. >1 Myr) mechanical behaviour of the oceanic lithosphere has come from studies of how it deforms in response to large loads such as volcanoes and sediments. A model widely used to explain the deformation is an elastic plate in which flexural rigidity depends on the thermal age of the lithosphere at the time of loading. An elastic model, however, is time-invariant and does not take into account temporal changes that may occur in the flexural rigidity as a consequence of loading. There is evidence, for example, that the flexural rigidity of the oceanic lithosphere also depends on load age, being large at short times and small at long times. Thus, competing effects may exist between thermal cooling which strengthens the lithosphere and some form of load-induced stress relaxation which weakens it. In order to investigate the relative roles of these processes, we have developed a multi-layered viscoelastic model which is based on the results of experimental rock mechanics that creep in the lithosphere is a thermally activated process, and on a thermal structure that is given by the plate-cooling model. By comparing the predictions of the model with a new compilation of flexural rigidity estimates, we have found that, if the upper mantle viscosity is 1020 Pa s, the activation energy that best describes the long-term mechanical behaviour of the oceanic lithosphere is 120 KJ mol-1. This parameter pair explains the dependence of flexural rigidity on both plate and load age. It also helps account for the subsidence and uplift history of oceanic islands and the stratigraphic patterns that develop in the flexural moats that flank them. At atolls, a multilayered viscoelastic model explains the rapid subsidence that follows shield building and does not require that the age of the lithosphere that supports a volcano is thermally 're-set' to a younger value. Our studies suggest that, while the oceanic lithosphere has viscoelastic properties, the viscosity of its upper layers is so much higher than that of its lower layers that in effect it behaves as a thin elastic plate on long timescales. There will therefore be a certain permanence to the observations of oceanic flexure such that they may be used, with some confidence, to evaluate the tectonic setting of individual features of the seafloor and, in some cases, their age.